Construction management - Halpin, Daniel W.; Senior, Bolivar A. (Hoboken, NJ : Wiley, 2012)
"The construction professional has to be a "jack of all trades, and master of all." This text covers a wide range of subjects, reflecting the breadth of knowledge needed to understand the dynamics of this large and complex industry. This edition introduces extended coverage in the scheduling area to address more advanced and practice oriented procedures such as Start to Start, Finish to Finish, and similar relationship between activities in a network schedule."--
Includes bibliographical references and index.
Keywords: Construction industry -- United States -- Management; Construction industry -- Law and legislation -- United States